Determining capital adequacy for a community bank's agricultural loan portfolio - Black, Kevin (Kansas State University, 2015)
As the recent financial crisis brought to light, the ability of commercial banks to quantify and better manage risk in their loan portfolios is paramount to their continued success and viability. Assessing, managing, and retaining capital is now a larger issue than ever given this event as well as the advent of the Basel III Accord. Pinnacle Bancorp is a community banking organization headquartered in Omaha, Nebraska with roughly $8.6 billion in assets. The company is also one of the largest agricultural lenders in the country and the largest agricultural lender among traditional community banks. Given the ominous outlook heading into 2016 for agricultural producers from lower projected net incomes and increased borrowing costs following Federal Reserve action on the Fed Funds Rate, many banks worry about the increased likelihood of default for agricultural producers. The objective of this thesis is to determine the adequacy of Pinnacle Bank’s equity capital relative to the agricultural loan portfolio. This process begins by employing binary logit regression in an effort to determine the probability of default for the bank’s agricultural loan portfolio. With default likelihood quantified, efforts are then made to determine the bank’s credit value-at-risk at various solvency levels. These figures are then compared to current capital levels in order to determine the adequacy of bank capital as measured by five key regulatory ratios ultimately imposed by Basel III. Finally, recommendations are made to management as to the adequacy of bank capital relative to the agricultural loan portfolio and any future efforts that need to be made in order to determine and ensure the adequacy of bank capital for the entire loan portfolio.
Keywords: Loan default; Stress test; Loan portfolio; Banking